A mosaic analysis in Drosophila fat body cells of the control of antimicrobial peptide genes by the Rel proteins Dorsal and DIF. - Manfruelli, P.; Reichhart, J.M.; Steward, R.; Hoffmann, J.A.; Lemaitre, B. (The EMBO Journal, 1999)
Expression of the gene encoding the antifungal peptide Drosomycin in Drosophila adults is controlled by the Toll signaling pathway. The Rel proteins Dorsal and DIF (Dorsal-related immunity factor) are possible candidates for the transactivating protein in the Toll pathway that directly regulates the drosomycin gene. We have examined the requirement of Dorsal and DIF for drosomycin expression in larval fat body cells, the predominant immune-responsive tissue, using the yeast site-specific flp/FRT recombination system to generate cell clones homozygous for a deficiency uncovering both the dorsal and the dif genes. Here we show that in the absence of both genes, the immune-inducibility of drosomycin is lost but can be rescued by overexpression of either dorsal or dif under the control of a heat-shock promoter. This result suggests a functional redundancy between both Rel proteins in the control of drosomycin gene expression in the larvae of Drosophila. Interestingly, the gene encoding the antibacterial peptide Diptericin remains fully inducible in the absence of the dorsal and dif genes. Finally, we have used fat body cell clones homozygous for various mutations to show that a linear activation cascade Spaetzle--> Toll-->Cactus-->Dorsal/DIF leads to the induction of the drosomycin gene in larval fat body cells.